Parental and children’s health behavior stemming from the Thai national health recommendations in Bangkok: 10.55131/jphd/2023/210105 - Cherdchoongarm, Kwansuda (Journal of Public Health and Development, 2022)
Non-communicable diseases (NCDs) have an impact on treatment costs and economic prosperity. Ten National Health Recommendations (NHRs) were announced by the Thai government in 1996 to promote the good health of children, adolescents, and the general public. Although regular practice of these recommendations should promote good health, the data from the Ministry of Health in 2015 shows that Thai children moderately following the NHR have higher health risk behaviors, potentially leading to obesity; a continually growing threat to Thai children, as well as increasing the risk of Type 2 diabetes and NCDs in adults. This research aims to study the promotion of good health by parents of students in primary schools in Bangkok under the NHRs and the relating factors. This study uses both quantitative and qualitative methods. The quantitative method is descriptive-comparative research conducted on the health promotion behavior of parents and children in three groups. These consist of schools under the Office of the Basic Education Commission (OBEC), the Bangkok Metropolitan Administration (BMA), and the Office of the Private Education Commission (OPEC). Multi-stage and stratified sampling are used to select 1,043 participants from eight schools in Bangkok, while the statistical analysis is conducted by one-way ANOVA. The qualitative method uses in-depth interviews with 12 parents and six school directors. According to the results, the health behavior of parents and students from the three schools showed statistically significant differences at the 0.05 level. In terms of health promotion, students with higher scores relating to NHRs on the questionnaire had parents with better health behavior than those with lower scores. The NHRs are used to organize knowledge-sharing sessions in schools.